The Effect of Music Therapy on Clients' Vital Signs during Pulmonary Function Test: An Experimental Study - Ala'a Hasan Jasim Al-Foa'adi, Mohammed Baqer Al-Jubouri, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The patient's vital signs must stay stable pre a pulmonary function test since the approach demands the patient to breathe slowly and deeply and exhale quickly. However, events that cause variations in normal vital signs may impact the patient. Many strategies can be utilized to stabilize vital signs, including music treatment. The purpose of this study is to compare the effectiveness of music therapy on the vital signs of client's pre a pulmonary function test. Methods: An experimental design study with an application (pre-test, post-test), to determine the effectiveness of music therapy for clients pre pulmonary function test for 106 clients in Al-Diwaniyah, Al-Shamiya, and Al- Hamza public hospitals In Iraq. Participant's vital sings (pulse rate, respiratory rate, blood pressure and oxygen saturation) were measured before and after the intervention group. Two groups assigned as music interventions and a control group. Results: The results showed the difference in Pulse rate between pre and post- test were decrease in Music therapy group 6.32 b/m. While Systolic blood pressure and Diastolic blood pressure were increased in Music therapy group 3.17/ 2.22 mm/hg respectively. Also the results showed the respiratory rate was decreased in Music therapy group 2.07 b/m. While oxygen saturation was increased in Music therapy group 2.20. Conclusions: Listening to music pre pulmonary function test had a positive effect on the regulation or stability of vital signs. Age and body mass index have the most influence on the vital signs of the clients who listed to music pre pulmonary function test.